Bank Loan Supply and Monetary Policy Transmission in Germany: An Assessment based on Matching Impulse Responses - Oliver Hülsewig; Eric Mayer; Timo Wollmershäuser (University of Würzburg, Department of Economics, 2004)
This paper addresses the credit channel in Germany by using aggregate data. We present a stylized model of the banking firm, in which banks decide on their loan supply in the light of uncertainty about the future course of monetary policy. Applying a vector error correction model (VECM), we estimate the response of bank loans after a monetary policy shock in consideration of the reaction of the output level and the loan rate. We estimate our model to characterize the response of bank loans by matching the theoretical impulse responses with the empirical impulse responses to a monetary policy shock. Evidence in support of the credit channel can be reported.
Keywords: E44; E52; 330; Monetary policy transmission; credit channel; loan supply; loan demand; minimum distance estimation; Kreditkanal; Kredit; Transmissionsmechanismus; Geldpolitik; Schock; Schätzung; Deutschland